Evaluasi Pembelajaran Mahasiswa di Masa Pandemi COVID-19 - Zico Fakhrur Rozi; Hadiwinarto Hadiwinarto (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to evaluate online learning during the COVID-19 pandemic for students of the Biology Education Study Program, STKIP-PGRI Lubuklinggau. This research method is a qualitative method using a questionnaire. The data collected includes the results of student satisfaction with online learning, online media used in online learning, the results of delivering material in online learning, deficiencies in online learning, students' choices of lecture methods. The results showed that students satisfied with online learning were as much as 30.2% and WhatsApp was the most popular media. The level of satisfaction with the delivery of material by lecturers was 39.7% and 39.7% of students stated that online learning was wasteful of quota, so the majority of students (49.2%) wanted learning to be carried out face-to-face. In conclusion, students are satisfied with online learning but want to immediately implement face-to-face learning in class. Keywords: COVID 19, Evaluation, Online Learning